VOC emissions from building materials: results from lab and model room trials. (August 2014) - Weigl, M.; Fürhapper, C.; Niedermayer, S.; Habla, E.; Nohava, M.; Nagl, S.; Polleres, S.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper reports on first results from a recently finished project dealing with indoor air quality in timber constructed houses. The FLEC method was applied measuring single building products with respect to their emission of VOCs (i.e. volatile organic compounds) on a small scale. Furthermore, total emissions are investigated in full scale model rooms (30 m3) equipped with variable panel product types and coverings. It has been shown that the total VOC (TVOC) value, consisting of a heterogeneous mixture of single substances (from 25 up to 68 within the test setup), decreases significantly with duration time. Within one year, ranking of the TVOC emission level for 26 individual building products including wood based panels, plasterboards, flexible insulations, adhesives, vapour barriers and sealing sheets changed. Approximately 30% of the single substances formed 80% of the TVOC fraction. This actually highlights the complexity of indoor air emissions from building products. Full scale box trials allowed a direct comparison of OSB and OSB that was covered by gypsum plasterboard. Whereas the TVOC level immediately after construction is higher for uncovered OSB, values of both construction setups decline rapidly. After 14 days and onto 19 weeks, TVOC values were comparable for uncovered and covered OSB within the test. Hence, plasterboards have only a small effect on TVOC levels, but are not capable of reducing VOC emissions from building products.